Innocent in death - Robb, J. D., 1950- (New York G.P. Putnam's Sons, 2007)
Investigating the baffling murder case of an ordinary and much-loSved private school teacher, New York City lieutenant Eve Dallas struggles to identify who may have wanted the death of an innocent man
Php 1297.50
Leisure reading
Donated by Gorriceta-Rojo family 12.11.18
Keywords: Dallas, Eve (Fictitious character) -- Fiction; Police -- New York (State) -- New York -- Fiction; Teachers -- Fiction; New York (N.Y.) -- Fiction